A Review On The Impact Of Green Supply Chain Management Practices On Firms Technological Innovation - Norailis Ab Wahab; Alhussain Alsuraihi; Syarizal Abdul Rahim (International Journal of Modern Agriculture, 2024)
Indexed by WOS